MENAKAR JURIMETRI DALAM SISTEM CIVIL LAW: ANALISIS TEORETIS DAN TANTANGAN PENERAPAN - Widjaja, Gunawan; Wagiman; Naiborhu, Mesa Indra (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The development of legal science has experienced a shift from a normative approach to an empirical approach, along with the increasing complexity of legal issues in society. jurimetri, as a quantitative approach to legal analysis, combines statistical and computational methods to understand patterns in court decisions and evaluate the effectiveness of regulations. Despite its rapid development in the common law system, its application in the civil law system still faces conceptual and practical challenges. The prescriptive nature of civil law and its reliance on codification are the main obstacles to adopting this method. This article discusses the extent to which jurimetrics can be applied in civil law legal systems, highlighting the fundamental differences between the two legal systems as well as the epistemological challenges that arise. The research utilizes a juridical-normative approach with a conceptual analysis of the relevance of jurimetrics in a written norm-based legal system. The results of the study show that although jurimetrics faces various obstacles, its application is still possible as a tool for legal analysis, especially in evaluating regulations, predicting legal trends, and increasing the efficiency of the justice system. Therefore, it is necessary to develop more flexible methods so that jurimetrics can contribute to the civil law legal system without sacrificing the principle of legal certainty.